Recycling of a spent residue-fluid-catalytic cracking catalyst into an adsorbent for the removal of copper(II) ions from wastewater - Chen, Ying-Chu; Yang, Wen-Xin (Journal of environmental chemical engineering, 2024)
The recycling of spent residue fluid catalytic cracking (RFCC) catalysts into adsorbents addresses both waste management and environmental pollution. Herein, we aimed to extract metals from spent RFCC catalysts, subject them to hydrothermal treatment and washing processes, and characterized by XRD, FT-IR, XPS, BET and SEM techniques, which also evaluating their efficiency as adsorbents. The spent RFCC catalyst was washed for 3 h and hydrothermally treated at 100 °C for 24 h, resulting in RFCC-A with a surface area of 81.77 m²/g and an average diameter of 66.81 nm, the cation-exchange capacities of up to 4300 – 5325 meq/100 g. The washing process removed 40 % – 46 % of vanadium and 12 % – 13 % of nickel. The derived adsorbent demonstrated a Cu(II) ion removal capacity of 120 mg/g from wastewater within 1 h at pH 4, and a total adsorption capacity of 831.68 mg/g after three regenerations. The primary removal mechanism was cation exchange involving electrostatic attraction. The manufacturing cost of the adsorbent was 59.5 USD/kg, equating to 0.50 USD/g Cu(II), with regeneration costs under 1 USD/g Cu(II). These findings indicate that using spent RFCC catalyst-derived adsorbents is cost effective and environmentally beneficial. [Display omitted] •Recycled spent residue fluid catalytic cracking as adsorbent and regenerated 2 times.•About 40–46 % V and 12–13 % Ni was extracted within 3 h washing process.•The adsorbent removed 120 mg/g Cu from water within 1 h reaction.•the adsorbent made by this study had 831.68 mg/g capacities in life time.•Costs of manufacturing the adsorbent is 59.5 USD/kg (equals to 0.50 USD/g Cu).